2003
DOI: 10.1186/1476-8518-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Generating neutralizing antibodies, Th1 response and MHC non restricted immunogenicity of HIV-I env and gagpeptides in liposomes and ISCOMs with in-built adjuvanticity

Abstract: For enhancing immunogenicity and develop vaccine strategies using peptide based constructs against HIV-1, a chimeric peptide containing V3 loop and transmembrane sequence of gp41 with two glycine motifs as spacer was constructed. The V3-gp41, gp41 peptide and p17 and p24 peptides separately or in a cocktail were entrapped with or without MA729 as an immunoadjuvant in liposomes or ISCOMs. The immunogenicity, antigen induced T-cell proliferation and cytokine profiles of various formulations were studied in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Studies showed that the properties of liposomes such as size, lipid composition and antigen encapsulation methods, etc. can skew Th1/Th2 antibody responses [28] , [29] , [48] , [49] , [16] . In our experimental setting, the only variable is the methods of LACK peptide formulation in liposome vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the properties of liposomes such as size, lipid composition and antigen encapsulation methods, etc. can skew Th1/Th2 antibody responses [28] , [29] , [48] , [49] , [16] . In our experimental setting, the only variable is the methods of LACK peptide formulation in liposome vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Our data may be explained, however, by the findings of others. Reports have suggested that while Th1-type cyto- kines exert an overall negative effect on systemic humoral responses (79,81), they can have a positive effect on the magnitude of neutralizing antibody responses (82), and that neutralizing antibody responses can occur concurrent with induction of Th1-polarized responses (83)(84)(85). In particular, our results (VN antibody concurrent with induction of CTL) with this defensin-antigen fusion construct in cattle bears striking similarity to the results obtained when in the mouse model, an experimental DNA vaccine expressing murine beta-defensin 2 (mBD2) as a fusion with the gp120 antigen of HIV-1 induced systemic and mucosal CTLs and neutralizing antibody to the HIV-1 envelope protein in i.d.…”
Section: Discussionmentioning
confidence: 99%
“…[ 74 ] It was found that the experimental vaccine formulations based on ISCOMs enable effective prevention and spreading of infectious diseases caused by various pathogens such as viruses, retroviruses, parasites, and bacteria. So far, antigens derived from influenza, [ 149 ] herpes simplex virus, [ 150 ] HIV‐1, [ 151 ] and Newcastle disease [ 148 ] have been used to formulate ISCOMs.…”
Section: Development Of Nano‐based Vaccinesmentioning
confidence: 99%